Análise da gestão do orçamento de vendas com a utilização do business intelligence: o caso Barilla - Mellaci, Márcio (2012)
Sales management in companies in a competitive and turbulent environment requires the use of management tools that can provide information that enables quick decisions to bring improvements in performance. The optimization of information flow associated with new information technologies can transform the business and also generate an organizational change that interferes in the relations of its members, reflecting the culture of the organization and productivity of its communicability. This essay aims to identify factors that generate improvements in the sales budget management through the use of Business Intelligence. The method used was an exploratory case study with a food importer and distributor in the pasta business (BARILLA). To do so, observations were taken on the development of procedures for sales forecasting and sales budget and how this information was transferred to the information system and finally how the managers used the information received. It was analyzed the theoretical frameworks on the sales management process and decision-making on information systems and the applicability of the business intelligence in managing the sales budget. The primary data collection was conducted through interviews with a questionnaire with mixed questions, because it allows greater flexibility in the study of the organization, addressed to managers and people connected to the area of sales, responsible for achieving the goals, frequency of information reception and the importance of speed of information in decision-making within the organization. From the identification of the results it was possible to identify the importance of integrating the sales budget into the information system and its implications for business management, but without exhausting the topic in all its applications on the subject, but rather, making an exploratory hermeneutic exercise on the holistic and meaningful characteristics of organizational events